2012
DOI: 10.26719/2012.18.10.1021
|View full text |Cite
|
Sign up to set email alerts
|

1021 Home-related injuries among children: knowledge, attitudes and practice about first aid among rural mothers

Abstract: Injuries to children arising from home accidents are an increasing community health concern. The aim of this cross-sectional study in Qalubeya governorate, Egypt was to measure the incidence and types of home injuries affecting rural children aged up to 12 years and to assess their mothers' knowledge, attitudes and practices (KAP) about first aid and its associated factors. An interview questionnaire was completed by 1450 rural mothers. The incidence of home injuries in the previous 4 weeks was 38.3% (57.5% we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
50
5
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 7 publications
(11 reference statements)
17
50
5
1
Order By: Relevance
“…The current study revealed that more than half of injured children (59.3%) were aged ≤ 3 years, this may be due to the younger the child , the higher the frequency of household injuries. This finding contradicted with (Eldosoky , 2011) who revealed that more than half of injured children (50.6%) were aged 9 -12 years. Regarding sex differences it was found that more than half of the injured children were boys (58.7%) than girls (41.3%) this result agrees with (Eldosoky , 2011) who found that the incidence rate of home accidents constituted (57.5%) for boys and (42.5%) for girls and also similar to study in Turkey (53.4% for boys and 46.6% for girls) and ( ztürk C et al, 2010 )who and also agreed with (Mahalakshmy et,al , 2011 ) who found that prevalence of injury was high among male children.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…The current study revealed that more than half of injured children (59.3%) were aged ≤ 3 years, this may be due to the younger the child , the higher the frequency of household injuries. This finding contradicted with (Eldosoky , 2011) who revealed that more than half of injured children (50.6%) were aged 9 -12 years. Regarding sex differences it was found that more than half of the injured children were boys (58.7%) than girls (41.3%) this result agrees with (Eldosoky , 2011) who found that the incidence rate of home accidents constituted (57.5%) for boys and (42.5%) for girls and also similar to study in Turkey (53.4% for boys and 46.6% for girls) and ( ztürk C et al, 2010 )who and also agreed with (Mahalakshmy et,al , 2011 ) who found that prevalence of injury was high among male children.…”
Section: Discussioncontrasting
confidence: 55%
“…This finding contradicted with (Eldosoky , 2011) who revealed that more than half of injured children (50.6%) were aged 9 -12 years. Regarding sex differences it was found that more than half of the injured children were boys (58.7%) than girls (41.3%) this result agrees with (Eldosoky , 2011) who found that the incidence rate of home accidents constituted (57.5%) for boys and (42.5%) for girls and also similar to study in Turkey (53.4% for boys and 46.6% for girls) and ( ztürk C et al, 2010 )who and also agreed with (Mahalakshmy et,al , 2011 ) who found that prevalence of injury was high among male children. Differences in regional and sample characteristics may affect the statistical significance of the impact of gender in injuries (Polat S et al, 2005) As regards types of home accidents the present study indicates that Cut/wound represented the highest percentage of home injury (37.3%) and this agrees with ( Abd El-Aty., et al, 2005) who indicated that wounds were the most common accidents among studied children was (37.4%).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…9,11 Similarly a study by Eldosoky et al revealed that 73.4% of the respondents knew about first aid and 56.1% reported that media was their primary source of information. 12 Almost 90% children received first aid either at home or nearby clinic, only 3% needed hospital admission. While in a report from Tripura 91.26% participants/parents said that they gave first aid to their children after any domestic injury.…”
Section: Discussionmentioning
confidence: 99%
“…An adequate amount of first aid knowledge can increase the chances of survival of the injured person. Since children spend most of their time at home, most of the accidents occur at home [7,8]. The most common types of accidents are; falls, burns, drowning, choking, cuts and wounds [7,9].…”
Section: Introductionmentioning
confidence: 99%